2019
DOI: 10.55500/jikr.v6i1.71
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Efektifitas dan Efisiensi Perbekalan Farmasi di Instalasi Kamar Operasi RSIG

Abstract: Ruang operasi merupakan tempat yang memiliki peranan yang sangat krusial di Rumah Sakit dan harus dikelola sebaik-baiknya, karena kegiatan operasi membutuhkan biaya perawatan, biaya operasi, dan biaya sumber daya yang tinggi. Ruang operasi menghabiskan biaya 9% dari anggaran tahunan rumah sakit. Pengeluaran terbesar di rumah sakit adalah untuk aktifitas ruang operasi, yaitu sekitar 40% dari 70% pengeluaran rumah sakit. Besarnya biaya operasi terjadi akibat banyaknya sumber daya yang digunakan untuk melaksanaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The ideal recovery room layout is one that is easily accessible to both the doctor and the operating patient. So that it can increase the effectiveness of the operating room and make it easier for service providers [31].In this study, it was also found that the operating room has its own room which is sufficient to store equipment, linen, pharmaceutical drugs including narcotics. The space for storing sterilized instruments and instruments is in a closed drum and stored in the instrument cabinet.…”
Section: Operating Room Layout Effectivenessmentioning
confidence: 74%
“…The ideal recovery room layout is one that is easily accessible to both the doctor and the operating patient. So that it can increase the effectiveness of the operating room and make it easier for service providers [31].In this study, it was also found that the operating room has its own room which is sufficient to store equipment, linen, pharmaceutical drugs including narcotics. The space for storing sterilized instruments and instruments is in a closed drum and stored in the instrument cabinet.…”
Section: Operating Room Layout Effectivenessmentioning
confidence: 74%